2017
DOI: 10.1186/s13054-017-1637-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ‘tidal volume challenge’ to improve the reliability of pulse pressure variation

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2017. Other selected articles can be found online at http://ccforum.com/series/annualupdate2017. Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http://www.springer.com/series/8901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…In fact, a similar approach has been already successfully used in patients undergoing forms of controlled ventilation to enhance the reliability of stroke volume variation and PP variation. Freitas et al increased the V T from 6 to mL to 8 mL/kg body weight for 5 min [37]; Reuter et al randomly applied 5, 10, and 15 mL/kg of V T [38] and, more recently, Myatra et al used a 1-min “V T -challenge”, increasing the V T from 6 up to 8 mL/kg [39]. Finally, the analysis of the slope for SAP nadir has previously been successfully applied in small cohorts of postsurgical patients [4042].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a similar approach has been already successfully used in patients undergoing forms of controlled ventilation to enhance the reliability of stroke volume variation and PP variation. Freitas et al increased the V T from 6 to mL to 8 mL/kg body weight for 5 min [37]; Reuter et al randomly applied 5, 10, and 15 mL/kg of V T [38] and, more recently, Myatra et al used a 1-min “V T -challenge”, increasing the V T from 6 up to 8 mL/kg [39]. Finally, the analysis of the slope for SAP nadir has previously been successfully applied in small cohorts of postsurgical patients [4042].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic use of hydroxychloroquine has not prevented COVID-19 illness when administered within four days post-exposure [26]. Furthermore, its usefulness for the treatment of COVID- 19 has not yet shown prom- ising results: a multicentre trial in non-severe COVID-19 patients showed no clinical improvement after 15 days of hydroxychloroquine. The groups included either hydroxychloroquine alone or in combination with azithromycin versus standard of care [27].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Thirty patients were nally included and analysed. The intra-observer variability of the measurement of IVCV at baseline was 9 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]%.…”
Section: Patientsmentioning
confidence: 99%
“…Another means to predict preload responsiveness in case of low Vt is to perform a "Vt challenge" [9]. It consists in transiently increasing Vt from 6 to 8 mL/kg of predicted body weight and observing the induced changes in PPV.…”
Section: Introductionmentioning
confidence: 99%